2017
DOI: 10.1016/j.jcm.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoma of the Cervical Spine: A Case Study

Abstract: Objective: The purpose of this case study is to describe the presentation of a patient with plasmacytoma. Clinical Features: A 49-year-old man presented with progressive neck pain, stiffness, and dysphagia to a chiropractic office. A radiograph indicated a plasmacytoma at C3 vertebral body. The lesion was expansile and caused a mass effect anteriorly on the esophagus and posteriorly on the spinal cord. Neurologic compromise was noted with fasciculations and hypesthesia in the right forearm. The patient was ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Marrow containing bones especially spine is typical site for SOP. Some recent published cases of spinal plasmacytoma like thoracic (T7-T9), cervical (C3), lumbar (L4) confirm this anatomical region and involvement with malignancy [10][11][12]. In our paper, we described an exceptional case of primary plasmacytoma with lumbar disc involvement.…”
Section: Parameters Patient's Values Reference Valuessupporting
confidence: 69%
“…Marrow containing bones especially spine is typical site for SOP. Some recent published cases of spinal plasmacytoma like thoracic (T7-T9), cervical (C3), lumbar (L4) confirm this anatomical region and involvement with malignancy [10][11][12]. In our paper, we described an exceptional case of primary plasmacytoma with lumbar disc involvement.…”
Section: Parameters Patient's Values Reference Valuessupporting
confidence: 69%
“…Several studies have reported the vertebrae to be the most common site of SBP [4,10,13]. Due to lesion compression, back and neck pain are commonly reported initial symptoms of SBP [4], which has been demonstrated by numerous published case reports [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Of these cases, patients reported pain on average 8 months prior to the diagnosis of SBP.…”
Section: Discussionmentioning
confidence: 99%
“…Bony collapse, and cord compression can result in significant neurologic compromise. Awareness of the symptoms of presentation: pain, progressive motor and sensory deficits, and myelopathy enhances the ability to make an early diagnosis and intervene surgically before catastrophic neurologic consequences occur [15]. Surgical techniques can vary based on the anatomic location and extent of local destruction caused by the neoplasm.…”
Section: Discussionmentioning
confidence: 99%